2014
DOI: 10.1158/0008-5472.can-13-2440
|View full text |Cite
|
Sign up to set email alerts
|

An Antibody–Drug Conjugate That Targets Tissue Factor Exhibits Potent Therapeutic Activity against a Broad Range of Solid Tumors

Abstract: Tissue factor (TF)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
157
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(181 citation statements)
references
References 37 publications
11
157
0
Order By: Relevance
“…Consistent with our observations, de Goeij and colleagues have recently demonstrated that high turnover of cytokine receptor type 2, Tissue Factor, enabled efficient intracellular delivery of ADC (44). Tissue Factor ADC effectively killed a tumor cell lines expressing as low as 2 Â 10 4 target molecules per cell (45). Taken together, our work and published data on Tissue Factor (44,45) indicate that high turnover proteins selectively expressed in tumors, but not in normal vital cells, may represent attractive ADC targets.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our observations, de Goeij and colleagues have recently demonstrated that high turnover of cytokine receptor type 2, Tissue Factor, enabled efficient intracellular delivery of ADC (44). Tissue Factor ADC effectively killed a tumor cell lines expressing as low as 2 Â 10 4 target molecules per cell (45). Taken together, our work and published data on Tissue Factor (44,45) indicate that high turnover proteins selectively expressed in tumors, but not in normal vital cells, may represent attractive ADC targets.…”
Section: Discussionsupporting
confidence: 90%
“…4B, D, and F, where duostatin-3-conjugated antibodies did not induce bystander kill. Whereas TF-011-MMAE induced potent bystander kill which was in line with results published previously (4,33). To study the target requirements needed for efficient intracellular drug delivery, a drug-linker that only affects antigen-expressing cells was preferred.…”
Section: In Vitro Cytotoxicity Induced By Duostatin-3-conjugated Tf supporting
confidence: 81%
“…TF-011-MMAE showed potent antitumor activity in xenograft models derived from a broad range of solid cancers, and an acceptable safety profile in nonclinical toxicity studies (4). TF-011-MMAE and unconjugated TF-011 induced efficient antibody-dependent cell-mediated cytotoxicity and inhibition of TF:FVIIa-dependent intracellular signaling, both of which may contribute to the antitumor activity of TF-011-MMAE.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations